PARENTAL PERSPECTIVES OF BARRIERS AND FACILITATORS TO ACCESSING EARLY INTERVENTION SERVICES FOR CHILDREN WITH AUTISM SPECTRUM DISORDER - Begaliyeva, Akzhibek (Nazarbayev University Graduate School of Education, 2024)
Accessing early intervention (EI) services is paramount for children with Autism Spectrum Disorder (ASD) to support their developmental needs. However, navigating the process of accessing these services presents numerous challenges for parents. This qualitative study aims to investigate the barriers and facilitators experienced by parents seeking EI services for their children with ASD in Kazakhstan. Data were collected through in-depth interviews with five parents of children with ASD, allowing for a comprehensive exploration of their experiences. Thematic analysis revealed several key findings. Parents described bureaucratic and administrative difficulties, including lengthy wait times, bureaucratic red tape, a lack of clarity regarding resource availability, a lack of qualified specialists, awareness and knowledge, limited resources, logistical difficulties, and cultural and social stigma surrounding autism. Additionally, challenges in obtaining disability certificates and accessing rehabilitation centers were highlighted, reflecting systemic deficiencies in the healthcare and social support systems. Despite these barriers, parents identified personal networks, persistence, and advocacy as key facilitators in accessing EI services. Support from organizations and the government was also acknowledged, albeit with limitations. The findings underscore the need for systemic changes to provide access to EI services for children with ASD in Kazakhstan. The findings have implications for policymakers, healthcare providers, and researchers in improving the accessibility and quality of EI services for children with ASD in Kazakhstan and similar contexts.
Keywords: Type of access: Embargo; early intervention services; autism spectrum disorder; barriers; facilitators; Kazakhstan